The Determinants of Active Aging for Improving Elderly Abilities - Palestin, Bondan; Kholifah, Siti Nur; Arna, , Yessy Dessy (Asian Journal of Pharmaceutical Research and Development, 2022)
An elderly group is a vulnerable group due to the aging process. The declining health conditions of the elderly have an impact on the increasing dependence of the elderly on family and society. The state of the elderly is healthy holistically and actively affects the productive elderly. Increasing productivity among the elderly is significant in reducing dependence on others. One of the efforts to increase productivity among the elderly is the empowerment process. This research consists of two stages, (1) analytical observational method and (2) Focus Group Discussion. researchers will follow up on the research by Productive Elderly Indicator Measuring Tool based on an android application. The results of the study showed that there was a significant effect of holistic health conditions on increasing ability with a coefficient value of 0.268 with a significance of 0.003 (p-value <0.05). A positive coefficient means that the more holistic health conditions, the greater the ability of the elderly. There is a significant effect of the active determinant on increasing ability with a coefficient value of 0.449 with a significance of 0.000 (p-value <0.05). The positive coefficient means that the more active determinants are, the greater the ability of the elderly. There is a significant effect of increasing the ability of productive elderly with a coefficient value of 0.720 with a significance of 0.000 (p-value <0.05). The positive coefficient means that the increasing ability of the elderly will increase productivity elderly.